Factors Affecting the Online Learning Outcomes of Higher Educational Institutions in Nepal - Duwal, Bal Ram (The International Research Journal of Management Science, 2023)
Purpose: This study primarily aims to examine and evaluate the factors affecting the outcomes of online classes during the COVID-19 pandemic period among university students in Nepal. Similarly, this study investigated management students’ perception of online management courses and explored the presence of factors that help to generate online learning outcomes in management courses and devise an online learning outcomes model. Methodology: Using a survey research design, the study applied a cross-sectional study in three out of eight universities that taught management courses. A purposive sampling method was applied to select the respondent students. Exploratory factor analysis was conducted to establish internal consistency and evidence of validity. To assess the responses to online classes, a multivariate linear regression analysis was used. Findings: Digital pedagogy, learning environment, ICT knowledge, COVID-19 context, ICT-friendly University and curriculum, and outcomes were identified as the factors from exploratory factor analysis. The overall students’ perceptions of the online management course had high reliability with Cronbarch’s alpha of 0.941. However, only three factors; digital pedagogy, learning environment, and ICT friendliness of university and curriculum were found to be significant as per the regression analysis. Originality/value: This study contributes to the management of higher educational institutions and the model can be used in future research. The findings will support on quality improvement of the online teaching mode. Implications: Nepalese universities have to work on the development of ICT infrastructure and courses should be redesigned with ICT features in mind for effective online learning. Furthermore, Nepalese higher educational institutions should step forward for institutional transformation, especially by following an ICT-friendly curriculum and structure with a gradual introduction of digital pedagogy in its regular courses.